Condicionamento fisiológico de sementes de Urochloa spp. - Oliveira, Thaisa Fernanda (2020)
Seed priming is an alternative to improve the performance of seeds that have germination problems, such as Urochloa spp. This work aimed to evaluate the effect of priming on seeds of Urochloa spp. submitted to different priming solutions and periods of priming, through evaluations of physiological and enzymatic expression. Also, evaluate the response of primed seeds after water deficit and saline stress. Two experiments were carried out, one with the specie Urochloa brizantha cv. Marandu and another with Urochloa ruziziensis cv. Ruziziensis, in a completely randomized design, with four replications, in a factorial scheme (5x3) +1, with five priming solutions, three periods and one control (not primed seeds). The seeds were submitted to priming for 12, 42 and 72 hours in distilled water, potassium nitrate solution, spermidine, gibberellin and sodium nitroprusside. It was determined: seed moisture; germination; first germination count; germination speed index; viable seeds remaining from the germination test; electrical conductivity; seed emergency; emergency speed index; analysis of the enzymes pyruvate decarboxylase, alcohol dehydrogenase, malate dehydrogenase, esterase, superoxide dismutase, catalase, peroxidase and alpha-amylase. For seeds primed in the 42 hours time, another experiment was carried out for each specie, in which the seeds were submitted to a condition of salinity and water deficit, in a factorial scheme (3x6), with three conditions of germination (water, water restriction with PEG and salinity with NaCl) and 6 treatments that constituted the five priming solutions (distilled water, potassium nitrate, spermidine, gibberellin and sodium nitroprusside) plus the control (not primed seed). For these experiments were evaluated: germination test on the seventh and twentieth day after sowing; germination speed index; viability through tetrazolium test of the remaining seeds from the germination test; and seedling length. Priming improves the physiological potential of seeds and the use of sodium nitroprusside as a priming solution, within 42 hours, provides greater quality for the seeds of Urochloa brizhanta cv. Marandu and Urochloa ruziziensis cv. Ruziziensis. Priming is an efficient technique that minimizes the negative effects of water restriction and salinity environment. Under these conditions, a lower percentage of dormant seeds and greater germination, vigor and plant development were observed when using sodium nitroprusside for both species.